Gromov - Hausdorff Convergence and Topological Stability for Actions on Wasserstein Hyperspaces - M. A. Morawo; M. L. Danyaro; A. S. Bailey; K. Y. Azeez (Journal of Applied Sciences and Environmental Management)
In this paper, we make use of topological stability from Gromov – Hausdorff view point to establish the Gromov – Hausdorff convergence and stability of induced actions on Wasserstein hyperspaces between maps.